LEGAL SECURITY OF THE ACTIVITY INTERNATIONAL AIRPORTS - Netska, Lyubov; Zagorodnyuk, Victoria; Duving, Valeria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: generalization of approaches to the legal support of the activities of international airports in order to take into account the best experience in Ukraine. Research methods: general-scientific (dialectical, analysis and synthesis, system-functional, analogies) and special research methods (comparative-legal, logical-legal, formal-legal) were used. Results: the importance of legal regulation of airport activity at the international, regional, national, and local levels is asserted; it is proven that state regulation is key to the functioning of international airports; notices the constant changes in the legal provision of international airports, which meet new challenges and contribute to their more efficient operation; it is proven that the introduction of higher standards affects the competitiveness of airports; the necessity of implementing the requirements of EU legal acts in the field of aviation in Ukraine is determined. Discussion: local acts of international airports allow to raise standards and implement own development strategies; minimum standards for airports provide for compliance with the provisions of international agreements in the field of aviation; state programs, concepts and strategies for the development of international airports contribute to the development of the network of such airports and the economic strengthening of states; the introduced sanctions in the field of aviation affect the activities of airports and oblige them to be implemented; the activities of international airports are related to air traffic and are subject to state regulation (standards, certification, tariffs, investments, profitability, etc.), which requires constant improvement. The author concludes that the activity of international airports is related to air traffic and is subject to state regulation (standards, certification, tariffs, investments, profitability, etc.), which requires constant improvement. States try to comply with the principles and provisions of international agreements and international standards by regulating airports at the national level. World practice shows that there are several levels of legal regulation of international airports: international, regional, national (state), and local (relevant to a particular airport). As a rule, highly competitive airports are subject to legal regulation at all of these levels. As Ukraine enters the common aviation area with the EU, it will be necessary for international airports in Ukraine to implement the aviation requirements of the EU Regulations.